2013
DOI: 10.1002/ajmg.a.35761
|View full text |Cite
|
Sign up to set email alerts
|

Obesity with associated developmental delay and/or learning disability in patients exhibiting additional features: Report of novel pathogenic copy number variants

Abstract: Obesity is a major threat to public health worldwide, and there is now mounting evidence favoring a role for the central nervous system (CNS) in weight control. A causal relationship has been recognized in both monogenic (e.g., BDNF, TRKB, and SIM1 deficiencies) and syndromic forms of obesity [e.g., Prader-Willi syndrome (PWS)]. Syndromic obesity arising from chromosomal abnormalities, that typically also affect learning and development, are often associated with congenital malformations and behavioral charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
1
30
0
2
Order By: Relevance
“…1,2,11,14,16 Obesity or overweight is noted in 17 patients (10 of 14 patients with a deletion, 5 of 6 with a duplication, and 2 of 2 with a point mutation) and has an onset during (late) childhood (Supplementary Table S1 online). Other prevalent symptoms are a wide range of behavioral problems (11 of 14 patients with a deletion, 6 of 6 with a duplication, and 2 of 2 with a point mutation), such as aggressive, autistiform, and hyperactive behavior; stereotypic hand movements; and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2,11,14,16 Obesity or overweight is noted in 17 patients (10 of 14 patients with a deletion, 5 of 6 with a duplication, and 2 of 2 with a point mutation) and has an onset during (late) childhood (Supplementary Table S1 online). Other prevalent symptoms are a wide range of behavioral problems (11 of 14 patients with a deletion, 6 of 6 with a duplication, and 2 of 2 with a point mutation), such as aggressive, autistiform, and hyperactive behavior; stereotypic hand movements; and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] It was suggested that perturbed TMEM18 expression in the brain, and particularly in the hypothalamus, would translate into aberrant feeding behavior. Doco-Fenzy et al 2 and d' Angelo et al 16 reported a total of six patients carrying 2p25.3 deletions who had ID associated with obesity. It is interesting to note that in the five patients with a deletion reported by Doco-Fenzy et al, all deletions resided on the paternal allele, suggesting a paternal effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A obesidade frequentemente está associada a outras alterações, incluindo malformações congênitas, dismorfias, distúrbios comportamentais e deficiência intelectual (6,11,12). Já foram descritas na literatura mais de 30 síndromes relacionadas à obesidade, entretanto a etiologia da maior parte dos casos permanece desconhecida (3,12).…”
Section: Obesidade Sindrômicaunclassified